Optical Coherence Tomography Findings (SD-OCT and OCTA) in Early-Stage Type 3 Neovascularization - Silva, Nisa (2021)
A 76-year-old male presented with a small hyperreflective density in the outer nuclear layer with subtle retinal pigment epithelium (RPE) elevation and few intraretinal cysts on spectral-domain optical coherence tomography (SD-OCT). Optical coherence tomography angiography (OCTA) confirmed the presence of a tuft-shaped intraretinal neovascular lesion. SD-OCT performed 2 months before showed a smaller RPE elevation at the same location without intraretinal fluid. A 79-year-old male presented with a small hyperreflective density in the outer retina surrounded by scant intraretinal fluid on SD-OCT and a bright vessel on OCTA, suggesting early-stage type 3 neovascularization. SD-OCT performed 2 months before showed a smaller hyperreflectivity at the same location, without intraretinal fluid. An 84-year-old female presented with hyperreflective foci in the outer retina overlying a serous pigment epithelium detachment (PED) with focal RPE disruption on SD-OCT. SD-OCT performed 2 months before showed the same hyperreflective lesion associated with a shallower PED. No neovascular lesions were found on OCTA after six injections of bevacizumab. To conclude, careful evaluation of SD-OCT allows for early detection of type 3 neovascularization at a pre-exudative stage. OCTA may be useful in confirming the presence of intraretinal neovascular lesion and monitoring response to anti-vascular endothelial growth factor agents.